Nitrogen and Ergosterol Concentrations Varied in Live Jack Pine Phloem Following Inoculations With Fungal Associates of Mountain Pine Beetle - Guevara-Rozo, Sydne; Hussain, Altaf; Cale, Jonathan A.; Klutsch, Jennifer G.; Rajabzadeh, Rahmatollah; Erbilgin, Nadir (Frontiers in Microbiology, 2020)
Bark beetles (Coleoptera: Curculionidae, Scolytinae) contain some of the most ecologically and economically important insect species of conifer forests due to their ability to kill a large number of trees during periodic outbreaks, with cascading consequences for ecosystem function (Kurz et al., 2008; Bentz et al., 2010; Hicke et al., 2012; Seidl et al., 2014). Fungal symbionts associated with bark beetles can amplify the beetles’ damage by promoting successful host colonization and development (Harrington, 2005; DiGuistini et al., 2007; Six and Wingfield, 2011; Six, 2012; Wang et al., 2013, 2014; Therrien et al., 2015; Cale et al., 2017; Zhao et al., 2019). In particular, fungal symbionts can facilitate beetle nutrition by either serving as a direct dietary substrate (e.g., ergosterol) , or indirectly concentrating host plant nutrients (e.g., nitrogen) (Ayres et al., 2000; Bleiker and Six, 2007; Goodsman et al., 2012). Although bark beetle species have multiple species of symbiotic fungi (Klepzig and Six, 2004; Klepzig et al., 2004; Roe et al., 2011a), how these fungi differ in the nutritional benefits they provide to the beetles is poorly understood.